AB0179 The specific inhibitor of RORγT transcriptional activity and TH17 polarization digoxin reduces the severity of adjuvant-induced arthritis. (23rd January 2014) - Cascão, R.; Vidal, B.; Fonseca, J.E.; Moita, L.F.
Abstract : Background: We have previously reported an increase of interleukin (IL)-17 levels during the first weeks of rheumatoid arthritis (RA) onset. Objectives: Our main goal here was to investigate whether administration of digoxin, a specific inhibitor of Th17 cells polarization, is able to attenuate inflammation in a rat model of adjuvant-induced arthritis (AIA). Methods: Digoxin was administered to AIA rats in the early phase (4 days after disease induction) or in the established phase of arthritis (11 days after disease induction). The inflammatory score, paw perimeter and body weight were evaluated during the period of treatment. Rats were sacrificed after 19 days of disease evolution and paw samples were collected for histological and immunohistochemical evaluation. Results: We found that digoxin administration significantly suppressed joint inflammation if administrated in the early phase of disease course. The histological and immunohistochemical evaluation revealed that digoxin treatment was not efficient in inhibiting the infiltration of immune cells within the joint, but it was able to reduce local immune cells proliferation, if administrated in the early phase of arthritis. Conclusions: Early inhibition of Th17 polarization ameliorates AIA but does not inhibit immune cell infiltration into the joints. Disclosure of Interest: None Declared